32. DILEMA KEBIJAKAN OPERASI MARE NOSTRUM TERHADAP ARUS MIGRASI DI ITALIA 2012 – 2015 - Almira Devina Phedra Phelia; Hermini Susiatiningsih; Andi Akhmad Basith Dir (Journal of International Relations Diponegoro, 2016)
Migration flows in Italy increased post-Arab Spring that happeneed in North Africa andthe Middle East. Libya as a major gateway shipments directly affected migrants from theArab Spring so that there is instability in the conditions of the region. Smugglers fromLibya used to send irregular migrants from Libya towards Italy. On the way to Italy, manymigrants suffered at sea, the vessel which carrying migrants was not worth with excesscapacity. Lampedusa tragedy claimed 360 people died at sea, the Italians immediatelyresponded by establishing an operations to rescue migrants named Operation MareNostrum. This rescue operation received a negative response from the other party, becausethe operation regarded as the cause of the high flows of irregular migration in Italy andspread to other EU countries, then causing a dilemma. Italy have to bear a very high cost torun the operation alone, but Italy still carry out such operations alone. This research triedto find the Italian reasons to run Operation Mare Nostrum and effectiveness of the policy.This research found that Operation Mare Nostrum done in obedience to comply the normand it was not so effective in its implementation.